RETRACTED: Energy transition for meeting ecological goals: Do economic stability, technology, and government stability matter? - Tang, Tao; Shahzad, Farrukh; Ahmed, Zahoor; Ahmad, Mahmood; Abbas, Shujaat (Frontiers in Environmental Science, 2022)
Unquestionably, energy transition, which entails increasing renewables in the energy mix, is among the most reliable strategies to discontinue the utilization of fossil fuels and achieve Sustainable Development Goals (SDGs). In this context, technological advancement can not only stimulate green energy supply but also promote resource efficiency for realizing ecological goals. Also, persistent long-term energy policies and uninterrupted investments are needed to progress on SDGs for climate control and sustainable development. Hence, factors such as economic and government stability are pertinent to implementing and governing energy strategies. Against this background, this study assesses the potential of energy transition in meeting ecological goals by taking into account the roles of economic stability, technology, and government stability in BRICS from 1992 to 2018. Using the second-generation Westerlund cointegration test, the study found a long-run association among variables. The findings from the Continuously Updated Fully Modified (CuP-FM) test disclosed that energy transition is effective in limiting the ecological footprint (EF) in BRICS. Alongside this, economic stability and technology reduce ecological degradation. In addition, government stability stimulates environmental sustainability, while population density decreases environmental sustainability. Finally, the implications of these conclusions for meeting SDGs are discussed and policy directions are provided.